Child and adolescent obesity and ADHD : psychological impact and bullying - Sandra María Bergþórsdóttir 1990- (2017)
Obesity is defined as an abnormal fat accumulation that could put a person’s health at risk. ADHD is a neurological disorder, which is usually diagnosed in childhood. Studies indicate that ADHD children have a higher BMI than non-ADHD children. Furthermore, studies on both ADHD children and on children with obesity show that both children with ADHD and children with obesity are more likely to have anxiety, emotional problems and be bullied then non-ADHD children and children not with obesity. Present study analyzes whether ADHD children in obesity, had other comorbid concerns than children in obesity that do not have ADHD. Participants in this study (N = 374) were patients at the Children's Medical Center in Iceland, who had undergone obesity treatment. Results showed no difference between BMI-SDS scores for those who had ADHD and other comorbid concerns and for those who did not have ADHD and other comorbid concerns. However ADHD children were more likely to have anxiety, emotional problems and be bullied than non-ADHD children. Results indicate that other comorbid concerns may not affect the obesity of ADHD children in this sample. However, there is a great need to investigate this further. Offita er skilgreind sem óeðlileg fitusöfnun sem getur haft skaðleg áhrif á heilsu einstaklings. ADHD er taugaþroskaröskun og er oftast greind í barnæsku. Rannsóknir sýna að börn með ADHD eru með hærri líkamsþyngdarstuðul (LÞS) en börn sem ekki eru með ADHD. Rannsóknir sýna að bæði börn með ADHD og börn með offitu eru líklegri til þess að vera með kvíða, lenda í einelti og eiga við tilfinningavandamál að stríða heldur en börn sem ekki eru með ADHD eða með offitu. Þessi rannsókn skoðaði hvort börn með ADHD og með offitu, hefðu annarskonar erfiðleika heldur en börn með offitu og ekki með ADHD. Þátttakendur rannsóknarinnar (N = 374) voru sjúklingar hjá Heilsuskóla Landspítalans og höfðu fengið meðferð við offitu. Niðurstöður sýndu að ekki var munur á LÞS hjá þeim sem voru með ADHD og annarskonar erfiðleika og hjá þeim sem ...